Accuracy of linear mandibular measurements on conventional and cone beam computed tomography reconstructed panoramic radiographs - Nidhi Pathak Chauhan; Nanditha Sujir; Anindita Saha; Deepak Chauhan; Junaid Ahmed; Keerthilatha Muralidhar Pai (Wolters Kluwer Medknow Publications, 2023)
Introduction: The aim of the study was to evaluate and compare the precision of dimensional measurements in digital panoramic radiographs (PRs) and cone beam computed tomography (CBCT)-generated panoramic images. Materials and Methods: Ten dry human mandibles were subjected to direct anthropometric measurements, digital panoramic radiography, and CBCT scans. Vertical and horizontal measurements were made between predetermined points by two observers. Paired t-test was applied for the comparative analysis. p value <0.05 was considered statistically significant. Analysis of variance (ANOVA) was done followed by post-hoc Bonferroni test to correlate the measurements got by the three modalities. Results: Except for two vertical measurements (V2 and V4) there was statistically significant difference in relation to all the measurements. The highest mean difference was observed in relation to H4, which was 12.60 mm lesser on digital PR in comparison to the anatomic measurements. Also, except for two vertical measurements V1 and V5, all the other measurements were underestimated by the digital PR.Conclusion: Measurement done in reconstructed PR and digital PRs in the region of posterior tooth-bearing region and condylar region are statistically similar.